A 12-month retrospective, descriptive study of Hout Bay Volunteer Emergency Medical Service, Cape Town, South Africa - Kahle, Jurgen Werner (Division of Emergency Medicine, 2020)
Background There is a growing need for Emergency Medical Services (EMS) globally and in Africa, as health services develop. The establishment and continued operation of volunteer ambulance services might assist with this need. This study provides a comprehensive overview of the operational activities of a volunteer ambulance service and forms a first step for further studies of this and other volunteer ambulance services. Objectives This study describes and quantifies the operational activities of Hout Bay Volunteer Emergency Medical Service (Hout Bay EMS) a volunteer ambulance service in Cape Town, South Africa for a one year period from 1 January to 31 December 2016. Methods This retrospective study describes call-outs, shifts and service demographics of Hout Bay EMS for 2016, using Provincial EMS dispatch data and shift records from Hout Bay EMS. Performance comparisons are drawn between Hout Bay EMS and Provincial EMS. Outcomes In the study period, there were 682 call-outs involving Hout Bay EMS, a total mission time of 951 hours worked over 119 shifts by 31 active members in 2016. Assault was the leading call-out type (18.40%); 58.24% of call-outs were Priority 2 (less urgent), and 39.30% of call-outs ended in no patient transport. Response times to Priority 1 call-outs were generally shorter for Hout Bay EMS than those of Provincial EMS within the Hout Bay area. Members largely preferred night shift to day shift by a factor of 4:1; the majority of shifts were worked by Basic Life Support (28.57%) and Intermediate Life Support (57.98%) qualified members compared to the relatively few shifts (13.44%) worked by Advanced Life Support members. This study shows that a small volunteer ambulance service mostly active on weekends can successfully complement the efforts of the larger, full-time provincial ambulance service it is dispatched by. This model could be replicated elsewhere to meet the growing need for emergency medical services.